1991
DOI: 10.14430/arctic1528
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Developmental, Behavioural and Physiological Adaptations of the Ringed Seal, <i>Phoca hispida</i>, to Life in the Arctic Winter

Abstract: Ringed seals, Phoca hispida, the smallest of the marine arctic pinnipeds, are one of only two seal species in the world adapted to life in the land-fast sea ice. The habitat is characterized by a stable ice platform forming in early winter and lies at latitudes subject to extreme low temperatures. The small body size of adults and semi-altricial pups are an unusual adaptation to cold, allowing ringed seals to use shelters that they construct in the snow overlying their breathing holes. These small subnivean st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 37 publications
0
75
0
Order By: Relevance
“…In the case of unusually cold winters, ice breakup occurs later than normal; thus, predation pressure may be increased because predators can remain on the ice, hunting seals, longer into the spring (Stirling and Derocher, 1993;Stirling et al, 1999). However, early ice breakup can also have negative effects on ringed seals: it may interrupt the lactation period and force pups into the water at an earlier age, resulting in increased energy expenditure, slow growth, and decreased overall fitness Smith et al, 1991;Smith and Harwood, 2001). In addition, warmer spring temperatures and early season rains can melt and degrade birth lairs, increasing exposure of pups to predators (Derocher et al, 2004;Stirling and Smith, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of unusually cold winters, ice breakup occurs later than normal; thus, predation pressure may be increased because predators can remain on the ice, hunting seals, longer into the spring (Stirling and Derocher, 1993;Stirling et al, 1999). However, early ice breakup can also have negative effects on ringed seals: it may interrupt the lactation period and force pups into the water at an earlier age, resulting in increased energy expenditure, slow growth, and decreased overall fitness Smith et al, 1991;Smith and Harwood, 2001). In addition, warmer spring temperatures and early season rains can melt and degrade birth lairs, increasing exposure of pups to predators (Derocher et al, 2004;Stirling and Smith, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout their circumpolar range, they are closely associated with sea ice for most of the year. Their preferred winter habitat is stable ice with ridging or hummocks that facilitate accumulation of snow cover to allow construction of subnivean lairs-conditions that commonly occur in landfast ice Stirling 1975, 1978;Hammill and Smith, 1989;Smith et al, 1991). However, several studies have also found ringed seals overwintering and breeding in drifting pack ice (Fedoseev 1975(Fedoseev , 1997Finley et al, 1983;Wiig et al, 1999).…”
Section: Ringed Sealsmentioning
confidence: 99%
“…Ice-associated seals may be particularly vulnerable to changes in the extent or concentration of arctic ice because they depend on pack-ice habitat for pupping, foraging, moulting, and resting (DeMaster and Davis, 1995). Ringed seals (Phoca hispida) and polar bears (Ursus maritimus), which prey on them, are the only marine mammals that regularly occupy extensive landfast coastal sea ice (Smith et al, 1991). Ringed seals require snow cover in which to construct subnivean birth lairs on the fast ice.…”
Section: Ice As An Important Substrate For Pinnipeds and Polar Bearsmentioning
confidence: 99%
“…Ringed seals rely on both the duration of the ice cover and the total precipitation to create sufficient snow depth for the building of subnivean lairs (Smith et al, 1991). In this case, while increased snowfall could be beneficial for the construction of lairs, especially on smoother ice with few pressure ridges or ice hummocks, a reduction in the amount and extent of fast-ice habitat could be detrimental.…”
Section: Linkages Between Changes In the Freshwater Budget And Marinementioning
confidence: 99%